Efektifitas Pemberian Terapi Akupuntur Terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Elsi Sopiyatul Fuadah; Rohayati Rohayati (FORIKES, 2022)
Acupuncture is a simple and effective complementary therapy. This study aims to determine the use of acupuncture therapy to treat hypertension. This study is a literature review using the Proquest, Sciencedirect, Pubmed, Taylor&Francis, and Google Scholar databases. The keywords used were